Urgence of Regulations for The Acquisition of Limited Company Share in Indonesia - Adhimastha, Bayu; Kagramanto, Budi; Prasetyowati , Endang (Riviera Publishing, 2023)
Acquisition is the takeover of a company by another company by taking over assets or shares. However, this can create obstacles to business competition and monopolistic practices regulated by Law. Therefore, regulations govern acquisitions, but there is still legal ambiguity in Law No. 40 of 2007 concerning Limited Liability Companies. This study uses the normative juridical research method. Normative legal research is a scientific procedure to find the truth based on the scientific logic of Law from a normative perspective. Arrangements regarding Acquisitions are clarified by regulating the business competition supervisory commission (KPPU) No. 1 of 2009 concerning pre-notification of mergers, consolidations and acquisitions. As well as the existence of Government Regulation No. 57 of 2010 concerning Mergers or consolidations as well as the acquisition of company shares which can result in monopolistic practices and unfair business competition, as well as Government Regulation No. 44 of 2021 concerning the implementation of Prohibition of Monopolistic Practices and Unfair Business Competition. It is necessary to reform regulations related to the acquisition of shares in a Limited Liability Company by establishing an Act accompanied by Government Regulations and other implementing regulations that support and do not conflict with the Act. In addition, KPPU needs to conduct a more thorough and selective assessment so as not to cause jealousy between one another.